A New Approach to the Spatialization of Religion: Changes in the Spatial Distribution of Religious Institutions in Debrecen (Hungary) between the Second Half of the Nineteenth Century and 2023 - Kozma, Gábor (Religions, 2023)
The aim of the article is to examine one of the neglected areas in the spatiality of religion, the spatial distribution of religious institutions and the changes that have taken place in this relation over time in the case of Debrecen, a specific city in Hungary, which has hosted several religions both in the past and present. The main findings are discussed in five subsections concentrating on five consecutive periods. During the period under study, the number of institutions run by churches increased steadily until the Second World War. This process was interrupted after the Second World War, and partly as a consequence of the world war (with the deportation of Jews to concentration camps) and partly due to the anti-religious nature of the socialist regime, there was a significant decline followed by a resumption of expansion after 1990. Regarding the location of the institutions within the city and its changes, there were significant differences between the various types of institutions (e.g., churches, administrative centres, kindergartens, elementary and grammar schools). Research primarily relied on document analysis and fieldwork.